(untitled) (Web of Teachers: Inderscience Research, 2025)
This article presents a model of students’ ability to design integrative lessons. Integrative lessons combine different disciplines and fields of knowledge to help students think more broadly, develop creative problem-solving skills, and develop practical skills. The main components of the model are the use of innovative methods in the educational process, the active participation of students and the use of interactive teaching methods. Through this model, students deepen their knowledge and gain practical experience in solving real-life problems.